Corumbataia britskii (Siluriformes: Loricariidae: Hypoptopomatinae) a new species from the upper Rio Paraná basin, Mato Grosso do Sul, Central Brazil - Ferreira, Katiane M.; Ribeiro, Alexandre C. [UNESP] (My University, 2007)
A new Hypoptopomatinae, Corumbataia britskii, is described based on specimens recently collected in a tributary of the upper Rio Paraná basin, Mato Grosso do Sul State, Brazil. Corumbataia britskii differs from its congeners by having a more depressed head profile (vs. a more rounded head profile in C. cuestae and C. tocantinensis), by having a more developed and conspicuous tuft of enlarged odontodes on the tip of the supraoccipital (vs. its reduced condition found in C. cuestae and C. tocantinensis), and by heaving a partially enclosed arrector fossae (vs. an almost completely enclosed arrector fossae in C. cuestae and C. tocantinensis). Copyright © 2007 Magnolia Press.
Keywords: Neotropical Region; Siluriformes; South America; Taxonomy; Upper Rio Paraná; Loricariidae; Odontodes